Relationship between high-speed rail and regional development: Lessons from Japanese benchmark cases - Kazuaki Hiraishi (Asian Development Bank Institute (ADBI), 2019)
High-speed rail (HSR) is not a "sufficient condition" but a "necessary condition" for regional development. Understanding how to use HSR for regional development is essential. Japan's Shinkansen (bullet train) has a 50-year history, and Japan has long attempted to utilize Shinkansen for regional development. In this paper, I will introduce Shinkansen-related regional development cases, including a national economic plan, tourism promotion, and development around Shinkansen stations. There are currently several HSR development plans in process around the world, especially in Asian countries. The Japanese experiences presented in this paper are informative and useful for these countries. I will introduce a case study concerning advising Kuala Lumpur-Singapore's HSR based on Japanese experiences, in particular the effectiveness of the "back-casting approach" for localization.
Keywords: L92; N95; O53; R58; 330; high-speed rail; regional development; Japan shinkansen